The Moment of a Rising Power: Indonesia’s Foreign Policy Activism, 2004-2014 - Mohamad Rosyidin (Mandala: Jurnal Ilmu Hubungan Internasional, 2021)
During the reign of Susilo Bambang Yudhoyono, Indonesia’s foreign policy showed a high level of global participation. It had been recognized as a pivotal state by the international community. It played an important role in many international issues ranging from international security, economy, democracy and human rights, to climate change. In addition, the robust economic growth and the defence budget policy had contributed to the road toward a rising power status. This paper is a critical review of the literatures on the moment Indonesia’s rise in international politics during the Yudhoyono presidency. The focus of this paper is to identify the driving factors behind the rise of Indonesia towards a global power. This paper concludes that ideational factors primarily the idea of the elite play a crucial role beyond the economic and military structures.